THE IMPACT OF ENTERPRISE RISK MANAGEMENT ON FIRM PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES - Lukianchuk, Genrikh (European Scientific Journal, ESJ, 2015)
In today’s hostile and highly volatile business environment, risk management is a stumbling block for every organization in each sector. Yet little is known about ERM’s effectiveness and even less research papers have focused on the analysis of relation between ERM and firm performance in SMEs. Therefore, this research paper focuses on the analysis of Enterprise Risk Management (ERM) in Small and Medium Enterprises (SMEs). The author uses the data obtained from FAME database that provides financial information on firms based in UK and Northern Ireland. 208 SMEs were selected according to different assumptions (predefined incorporation dates, availability of cashflow reports, profit and loss statements etc.) and analyzed. Independent variables like the amount of auditor fees, quality score, the male/female board of directors proportion, board structure were selected as they could explain the volatility of cashflow (CF) and return on assets, respectively. Seemingly unrelated regression (SUR) was chosen as a method to allow for contemporaneous correlation between errors in these 2 regression models. Results drew various conclusions (i.e. number of executive directors has positive impact on performance, but also raises the level of cashflow volatility). However, no significant relation was found between СА and ROA using this set of variables that opens a field for future researches in this area. Finally, research paper provides a plethora of useful practical implementations for key stakeholders who are interested in the development of SMEs (investors, banks, government regulators etc.).